Longitudinal Examination of COVID-19 Public Health Measures on Mental Health for Rural Patients With Serious Mental Illness. Issue 9 (28th August 2021) - Riblet, Natalie B; Stevens, Susan P; Shiner, Brian; Cornelius, Sarah; Forehand, Jenna; Scott, Robert C; Watts, Bradley V
ABSTRACT: Introduction: There is emerging evidence to support that the COVID-19 pandemic and related public health measures may be associated with negative mental health sequelae. Rural populations in particular may fair worse because they share many unique characteristics that may put them at higher risk for adverse outcomes with the pandemic. Yet, rural populations may also be more resilient due to increased sense of community. Little is known about the impact of the pandemic on the mental health and well-being of a rural population pre- and post-pandemic, especially those with serious mental illness. Material and Methods: We conducted a longitudinal, mixed-methods study with assessments preceding the pandemic (between October 2019 and March 2020) and during the stay-at-home orders (between April 23, 2020, and May 4, 2020). Changes in hopelessness, suicidal ideation, connectedness, and treatment engagement were assessed using a repeated-measures ANOVA or Friedman test. Results: Among 17 eligible participants, 11 people were interviewed. Overall, there were no notable changes in any symptom scale in the first 3-5 months before the pandemic or during the stay-at-home orders. The few patients who reported worse symptoms were significantly older (mean age: 71.7 years, SD: 4.0). Most patients denied disruptions to treatment, and some perceived telepsychiatry as beneficial. Conclusions: Rural patients with serious mental illness may be fairly resilient in the face of the COVID-19 pandemic when they have access to treatment and supports. Longer-term outcomes are needed in rural patients with serious mental illness to better understand the impact of the pandemic on this population.